Glucocorticoid enhancement of memory storage involves noradrenergic activation in the basolateral amygdala - Quirarte, Gina L. (The National Academy of Sciences of the USA, 1997)
Evidence indicates that the modulatory effects of the adrenergic stress hormone epinephrine as well as several other neuromodulatory systems on memory storage are mediated by activation of β-adrenergic mechanisms in the amygdala. In view of our recent findings indicating that the amygdala is involved in mediating the effects of glucocorticoids on memory storage, the present study examined whether the glucocorticoid-induced effects on memory storage depend on β-adrenergic activation within the amygdala. Microinfusions (0.5 μg in 0.2 μl) of either propranolol (a nonspecific β-adrenergic antagonist), atenolol (a β(1)-adrenergic antagonist), or zinterol (a β(2)-adrenergic antagonist) administered bilaterally into the basolateral nucleus of the amygdala (BLA) of male Sprague–Dawley rats 10 min before training blocked the enhancing effect of posttraining systemic injections of dexamethasone (0.3 mg/kg) on 48-h memory for inhibitory avoidance training. Infusions of these β-adrenergic antagonists into the central nucleus of the amygdala did not block the dexamethasone-induced memory enhancement. Furthermore, atenolol (0.5 μg) blocked the memory-enhancing effects of the specific glucocorticoid receptor (GR or type II) agonist RU 28362 infused concurrently into the BLA immediately posttraining. These results strongly suggest that β-adrenergic activation is an essential step in mediating glucocorticoid effects on memory storage and that the BLA is a locus of interaction for these two systems.